Phosphorus fractions and its potential release in the sediments of Koycegiz Lake, Turkey - Yalçın Şahin (Lakes Reservoirs and Ponds, 2012)
This study was conducted to find out the seasonal and spatial patterns of the phosphorus in the littoral sediment and its potential release into the Koycegiz Lake, south west Turkey, between November 2011 and March 2012 at two months intervals. The scanning electron microscopy was used for elemental compositions of the sediment. The amounts and forms of phosphorus (P) in surface sediments of Koycegiz Lake were examined using a not sequential chemical extraction procedure. Four fractions of sedimentary P, including organic bound phosphorus fraction (Org≈P), calcium bound phosphorus fraction (Ca≈P), iron+aluminium bound phosphorus fraction (Fe+Al≈P) and carbonate bound phosphorus fraction (CO3≈P) were separately quantified. The results indicated that the contents of different phosphorus fractions in the sediments varied greatly. The proportion of phosphorus fractions was estimated as Org≈P (90.20 %), this fraction was followed by Ca≈P) (9.06 %), Fe+Al≈P (0.47 %) and CO3≈P (0.27 %) in this study. The level of phosphorus release from the sediment to the lake is calculated as low. The sediment phosphorus release fluctuated between -6.647–75.883 μg/m2.d-1 and the total phosphorus (TP) concentrations of the sediment samples were changed between 980.39 μg/gDW (Dry Weight) - 1990.81 μg/gDW. The results show that it can be evaluation as eutrophic for Koycegiz Lake.